#TITLE_ALTERNATIVE# - MARWAN (NIM : 12405021), MUHAMMAD
Target interval in the M field is under the seismic resolution so that the interpretation of seismic data which resides in the time domain will be very difficult to do. Spectral Decomposition is a technique to overcome this problem by analyzing the signal in the interpretation of the seismic data in the frequency domain.Continous wavelet transformation method is used in spectral decomposition method capable to decomposition time to frequency. The process of frequency of time signal obtained from the convolution with the wavelet with serves as wavelet analysis window that is affected by the scale and translation parameters. Scale and translation parameters that determine the frequency and time resolution. Spectral Decomposition techniques can combine with 3 input frequency characteristic red color associated with a low frequency, the frequency of green to the middle and blue for high frequency, called the Spectral Decomposition Red Green Blue. This technique is used to gain temporal thickness at the time of cross section of the target, Field M. By applying this method, the pattern of the channel and the other a thin layer can be seen.